2014
DOI: 10.1093/cvr/cvu040
|View full text |Cite
|
Sign up to set email alerts
|

miR126-5p repression of ALCAM and SetD5 in endothelial cells regulates leucocyte adhesion and transmigration

Abstract: miR126-5p is a functional, endothelial-enriched microRNA that participates in the control of leucocyte trafficking by regulating the expression of ALCAM and SetD5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
(44 reference statements)
3
44
0
Order By: Relevance
“…Lymphocyte extravasation is a multistep process that involves rolling, adhesion, and transmigration (42). ALCAM does not directly participate in leukocyte adhesion to endothelium in a model consisting of THP-1 monocytes interacting with human umbilical vein endothelial cells (HUVECs) (15). However, ALCAM regulates actin dynamics during the lymphocyte-endothelium cross talk (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocyte extravasation is a multistep process that involves rolling, adhesion, and transmigration (42). ALCAM does not directly participate in leukocyte adhesion to endothelium in a model consisting of THP-1 monocytes interacting with human umbilical vein endothelial cells (HUVECs) (15). However, ALCAM regulates actin dynamics during the lymphocyte-endothelium cross talk (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…ALCAM is expressed on endothelia and epithelia, where it participates in tissue development and maintenance (13); CD6 is not expressed on endothelia (14). ALCAM downregulation on primary human umbilical vein endothelial cells reduces monocyte transmigration (15). Conversely, ALCAM overexpression on endothelia or epithelia usually enhances cell extravasation and metastasis (14,16).…”
mentioning
confidence: 99%
“…Isolation of CD31 ϩ Cells-CD31ϩ cells were purified from mouse lungs using anti-CD31-coated magnetic Dynabeads (Life Technologies) exactly as described in (23).…”
Section: Methodsmentioning
confidence: 99%
“…5A). This point was particularly important because miR126-3p and miR126-5p are embedded within the egfl7 gene seventh intron, and both are known to affect endothelial cell activation (22,23). The effects of siEgfl7 in HUVEC could be rescued by overexpressing Egfl7 by the means of an expression plasmid.…”
Section: Tnf␣-induced Endothelial Cell Activation Is Repressed By Endmentioning
confidence: 99%
“…Similar to other coding genes, ALCAM works as the downstream target gene of miRNAs. Previous studies showed that ALCAM is regulated by miR-9, miR-483-5p and miR-126-5p and always relevant to invasive behavior in different tumors [26-28]. While, if ALCAM regulates the proliferation and invasion capacity of PAs cells and is regulated by miRNAs still remains unknown.…”
Section: Introductionmentioning
confidence: 99%